Penerapan Model Problem Based Flipped Classroom Dalam Pembelajaran: Sebuah Kajian Literatur Dan Sistematik - Aisya Purnomo, Putri Eodytha; Agustini, Ketut; Suartama, I Kadek (Cetta: Jurnal Ilmu Pendidikan, 2025)
The purpose of this research is to study how the Problem Based Learning model combined with the Flipped Classroom approach is applied in education. To conduct this research, the Systematic Literature Review (SLR) method was used. This method consists of fifteen scientific articles published between 2021 and 2025 in national and international journals covering various fields of study and educational levels. Quantitative, qualitative, and mixed methods approaches are used in these articles. The analysis results show that the use of problem based flipped classroom has become a highly relevant and aligned learning approach with the demands of future curricula, which require broad and sustainable student skills. Problem-based flipped classroom has now become an innovative model that can address contemporary educational challenges and enrich the learning process and outcomes across various levels and fields of study thanks to this new contribution. Nevertheless, implementation challenges such as teacher readiness and the availability of digital media are still encountered. This study concludes that problem based flipped classroom model is a creative learning approach useful for addressing the challenges of 21st-century education. It is hoped that these findings will provide theoretical and practical contributions to developing contextual, adaptive, and collaborative learning strategies.